2022
DOI: 10.1007/s00296-022-05146-9
|View full text |Cite
|
Sign up to set email alerts
|

Herpesvirus infections and post-COVID-19 manifestations: a pilot observational study

Abstract: The global spread of SARS-CoV-2 points to unrivaled mutational variation of the virus, contributing to a variety of post-COVID sequelae in immunocompromised subjects and high mortality. Numerous studies have reported the reactivation of "sluggish" herpes virus infections in COVID-19, which exaggerate the course of the disease and complicate with lasting post-COVID manifestations CMV, EBV, HHV6). This study aimed to describe clinical and laboratory features of post-COVID manifestations accompanied by the reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
73
1
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(81 citation statements)
references
References 35 publications
1
73
1
6
Order By: Relevance
“…Reactivated viruses, including EBV and HHV-6, have been found in patients with long COVID 18 , 21 , 22 , 27 (and have been identified in ME/CFS 45 ), and lead to mitochondrial fragmentation and severely affect energy metabolism 46 . A recent preprint has reported that EBV reactivation is associated with fatigue and neurocognitive dysfunction in patients with long COVID 22 .…”
Section: Major Findingsmentioning
confidence: 99%
“…Reactivated viruses, including EBV and HHV-6, have been found in patients with long COVID 18 , 21 , 22 , 27 (and have been identified in ME/CFS 45 ), and lead to mitochondrial fragmentation and severely affect energy metabolism 46 . A recent preprint has reported that EBV reactivation is associated with fatigue and neurocognitive dysfunction in patients with long COVID 22 .…”
Section: Major Findingsmentioning
confidence: 99%
“…In total, as of September, according to the Ministry of Health of Ukraine, and confirmed by the World Health Organization, there have been 454 attacks on health care facilities in Ukraine, more than 906 health care facilities are in need of restoration, and more than 123 destroyed (Figure 2 [6,9,10]. In September, the new academic year began in a hybrid form online (for students of the 5th year) and offline (for students of the 6th year, interns and doctors of the advanced training course).…”
Section: Resultsmentioning
confidence: 99%
“…Patients with Long/Post COVID manifestations presented with reactivation of EBV in 42.6%, HHV6 in 25.0%, and EBV plus HHV6 in 32.4% of the cases. Compared with controls, patients with herpes virus infections presented with significantly more symptoms of Long/Post COVID, elevated CRP and D-dimer, and suppressed cellular immune response 42 . These results indicate a potential involvement of reactivated herpes virus infections, in severe COVID-19 and formation of Long/Post COVID.…”
Section: Introductionmentioning
confidence: 85%